Evaluation of the quality of prescriptions with antibiotics in the government hospitals of Yemen - Al-Shami, Abdulkareem Mohammed; Ibrahim, Mohamed Izham M; Abdo-Rabbo, Ahmed (JCDR Research and Publications (P) Limited, 2011)
Introduction: Irrational prescribing is a habit which is difficult to counteract and this may lead to ineffective treatment, health risks, patient non-compliance, drug wastage, wasting resources and needless expenditure. Objective: The aims of this study were to investigate the prescribing of antibiotics in Yemen and provide a baseline picture of prescribing habits. It presented an overview on the quality of prescribing and the resulting patterns coming from the prescriptions. Methods: The scope of the study was limited to four public quaternary health care facilities in Sana’a, Yemen. A prospective drug utilization review method was used in this study. Results: Results showed that the total number of brand name antibiotics prescribed was 76.8%, and 27.5% of the antibiotics were not on the Yemen Essential Drug List (YEDL). Out of all prescriptions, it was found that 51.0% contained antibiotics. Antibiotic prescriptions were lacking in many areas of important information: the diagnosis, patient’s name, gender and age as well as for the prescribed antibiotics information (strength, dosage form, dose, frequency and duration). The average number of antibiotics per each patient received was 1.2 ± 0.4(median = 1) and the percentage of antibiotics prescribed as injections was 27.8%. Conclusion: The patterns which emerged in prescribing showed that there were various potential problems in antibiotic usage in the government quaternary hospitals in Yemen. Advocacy, education and awareness initiatives are required to alleviate these problems.